Coconut mealybug Nipaecoccus nipae (Maskell)(Insecta: Hemiptera: Pseudo coccidae) - Adriana Espinosa; Amanda Hodges; Gregg Hodges; Catharine Mannion (EDIS)
EENY-448, a 5-page illustrated fact sheet by Adriana Espinosa, Amanda Hodges, Greg Hodges, and Catharine Mannion, is part of the Featured Creatures collection. It describes this widely distributed pest with a wide host range that may be economically damaging to palms and tropical fruit crops — its distribution, field characteristics, life cycle, hosts, general plant damage, and management. Includes references. Published by the UF Department of Entomology and Nematology, June 2009.